PENGARUH PELATIHAN, KOMPETENSI DAN MUTASI TERHADAP SEMANGAT KERJA PEGAWAI YANG DIMEDIASI OLEH MOTIVASI KERJA PEGAWAI DI KEMENTERIAN KETENAGAKERJAAN RI AREA JAKARTA DAN BEKASI - Budiono, Tony Agus; Supriyadi, Edy; Putriana, Lies (SEKOLAH PASCASARJANA PRESS, 2019)
The purpose of this study was to determine the effect of training, competence and mutation on work motivation and work morale and prove the hypotheses about the relationship of research variables: competence, motivation, mutation, training and work morale. The population of this study was all Civil Servants in the Directorate General of Productivity Development and Training, Ministry of Manpower in the Jakarta and Bekasi Areas, which recorded a total of 303 employees. The total sample of the population is 173 Civil Servants taken using the Stratified Random Sampling technique. The statistical method used in this study is Structural Equation Modeling (SEM) which is operated through the LISREL program. In this study resulted that the variables of training, competence, and mutation have a positive and significant effect on work motivation and morale.